Providing meaningful activities for residents. (2nd June 2019) - Ashurst, Adrian
Abstract : Keeping busy and continuing to pursue interests are important components in improving care home residents' quality of life. Adrian Ashurst talks about how he trains care staff to organise these activities and suggests some ideas.